Assessing the use of e-business strategies by SMEs in Ghana during the Covid-19 pandemic - Rosina Naab; Anita Bans-Akutey (Annals of Management and Organization Research, 2021)
Purpose: The main purpose of this quantitative research was to assess various e-business strategies implored by small and medium enterprises (SMEs) in Ghana during the Covid-19 pandemic. Research methodology: It made use of a descriptive design. Data was collected with the use of a structured questionnaire, analysed with excel and presented in tables and figures. Results: The study revealed that small business owners have knowledge of e-business models with the most popular e-business model used being the Business to Consumer (B2C) model, while the least used model was the Business to Government (B2G) model. While imploring the use of e-business models and strategies, SMEs were faced with the challenge of very limited knowledge on the use of e-business strategies. Limitations: The study was limited to businesses in the Tema Metropolitan Assembly of Ghana. Contribution: Most of the SMEs were established in the traditional setting of business operations therefore there was little or no plan for integrating the internet in their operations. However, the pandemic has shifted their attention to adopting some virtual traction to their businesses for the benefit it offers such as continuous sales and more visibility. Further research on how each of the various concepts was used by SMEs is highly recommended.